Continuous On-Line Tar Measurements for Gasification Process Monitoring using Fluorescence Excitation-Emission Matrices at Elevated Temperature (Baghdad Science Journal, 2021)
Biomass has been extensively investigated, because of its presence as clean energy source. Tars and particulates formation problems are still the major challenges in development especially in the implementation of gasification technologies into nowadays energy supply systems. Laser Induced Fluorescence spectroscopy (LIF) method is incorporated for determining aromatic and Polycyclic Aromatic Hydrocarbons (PAH) produced at high temperature gasification technology. The effect of tars deposition when the gases are cooled has been highly reduced by introducing a new concept of measurement cell. The samples of PAH components have been prepared with the standard constrictions of measured PAHs by using gas chromatograph (GC). OPO laser with tuning rang of (200 to 2400) nm and peak energy of 2.2 mJ were used to excite the tar compounds, which have fluorescence properties in the range of ultraviolet| blue spectral range. The measurements have been evaluated by incorporating the Excitation-Emission Matrices (EEM), presented as time consuming method for tar monitoring.